2007
DOI: 10.1136/jnnp.2007.132100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of collateral flow on tissue fate in acute ischaemic stroke

Abstract: Background-Collaterals may sustain penumbra prior to recanalisation yet the influence of baseline collateral flow on infarct growth following endovascular therapy remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
306
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(323 citation statements)
references
References 12 publications
15
306
1
1
Order By: Relevance
“…The predictive value of the morphologic extent is consistent with previous reports using dynamic CTA and other imaging techniques. 4,14,26 Notably, both delay and extent remained independent predictors after correcting for IV thrombolysis and mechanical thrombectomy. This suggests the beneficial effect of good collateralization in dynamic CTA, even in the absence of interventions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The predictive value of the morphologic extent is consistent with previous reports using dynamic CTA and other imaging techniques. 4,14,26 Notably, both delay and extent remained independent predictors after correcting for IV thrombolysis and mechanical thrombectomy. This suggests the beneficial effect of good collateralization in dynamic CTA, even in the absence of interventions.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, this is the first study to quantitatively show a predictive value of the collateral blood flow delay independent of the morphologic collateral grade. Qualitative assessment of hemodynamic and morphologic parameters of leptomeningeal collaterals has been used in catheter angiography grading systems and has been shown to predict a favorable outcome, [24][25][26] showing the importance of enhancement time for collateral quality. Saito et al 27 assessed the correlation of transit time from the ICA to the M2 segment with the lesion size on follow-up NECT.…”
Section: Discussionmentioning
confidence: 99%
“…Besides lysis of the obstruction, thrombolytics also reverse stasis-induced thrombosis distal to the occlusion. However, access depends on the extent of the pial collateral circulation (Brozici et al, 2003;Liebeskind, 2005), yet patients with acute occlusion evidence wide variation in the extent of retrograde perfusion of the MCA tree (Bang et al, 2008;Christoforidis et al, 2009). Whether this is due to individual variation in the pial collateral circulation or thrombotic or other mechanisms is unclear because current imaging methods cannot resolve these small vessels in humans, and until now, no animal studies had been done.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde perfusion of the distal MCA in patients suffering acute obstruction of its trunk varies substantially (Bang et al, 2008;Christoforidis et al, 2009), presumably in part from differences in the extent of the preexisting pial collateral circulation. The contribution of genetic differences to such variation is unknown.…”
Section: Wide Genetic Variation In the Extent Of The Native Pial Collmentioning
confidence: 99%
“…Clinical data were prospectively collected on a web-based registry, including demographic data, symptoms onset, time of arrival at the Emergency Department, acute phase parameters, blood examination, National Institute of Health Stroke Scale (NIHSS) astreatment (ET) is a key element to achieve a favourable outcome. In the acute pre-treatment phase of ischaemic stroke, collateral circulation allows the complete or partial perfusion of the ischaemic area beyond the clot, and contributes to the survival of the ischaemic penumbra 4 . Some authors found that pial collateral circulation at digital subtraction angiography was correlated with the reduction of the infarcted area in 36 patients with middle cerebral artery (MCA) occlusion 5 and that good collateral circulation resulted in less severe neurological deficits at baseline 6 .…”
Section: Methodsmentioning
confidence: 99%